The critical link CHRs & traumatic brain injury in Indian country - New Mexico Aging & Long-Term Services Department (Santa Fe, NM State of New Mexico, U.S. Department of Health and Human Services., 2010)
This DVD provides education to Native American Community Health Representatives to improve their awareness and recognition of Traumatic Brain Injury (TBI), its prevalence in Indian Country, and the special rules that CHRs can play on behalf of American INdians/Alaska Natives with brain injury to facilitate medical treatment and service delivery, and ultimately improve recovery outcomes for their patients.
Brain injury awareness for community health representatives.
Keywords: Traumatic Brain Injury - Native Americans. -- Traumatic Brain Injury - Awareness